Reliability of Diagnosis of Acute Appendicitis by Clinical Assessment Through Modified ALVARADO Vs RIPASA Scoring System at Combined Military Hospital, Rawalpindi - Rohan Qamar; Khalid Mahmood; Romassa Javed; Faheem Sher; Ibrahim Tufail (Life and Science, 2024)
Objective: To determine the diagnostic accuracy of RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) and Modified ALVARADO score in the diagnosis of acute appendicitis by using histopathology as a gold standard. Study Design: A comparative cross-sectional study. Place and Duration of Study: The study was carried out at the Department of Surgery, Combined Military Hospital (CMH) Rawalpindi, Pakistan from January 2020 to August 2020. Methods: A total of 126 patients suspected of having acute appendicitis were included. All patients who had met the inclusion criteria were chosen via the process of consecutive sampling. Patients who had presented with right iliac fossa pain, migration of pain, anorexia, nausea, and vomiting and were admitted to the hospital were assessed prospectively using RIPASA and Modified ALVARADO scores. RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) score > 7.5 and Modified ALVARADO score > 7 were used to diagnose acute appendicitis. The diagnosis was confirmed postoperatively using a histopathological report. Every scoring system was assessed for validity by calculating sensitivity, specificity, diagnostic accuracy, negative predictive value, and positive predictive value. Result: The results obtained from individuals recruited in the study showthat out of 126 patients, 70(55.6%) were male and 56(44.4%) were female. The mean age was 33.25±8.19 years. 83.3% of patients having RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) score (≥7.5) and 68.3% of patients having Modified ALVARADO score (≥7) have met the criteria for acute appendicitis. The sensitivity and specificity of the RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) score were 90.9% and 73.3% compared with 73.8% and 73.3% of the Modified Alvarado score. Conclusion: The RIPASA (Raja Isteri Pengiran Anak Saleha Appendicitis) scoring system is a more convenient, accurate, and specific scoring system for our population than the Modified ALVARADO scoring system.